The Development of Digital Media Based on Mandar Local Culture to Enhance Curiosity and Scientific Literacy of Physics Candidates - Batiran, Dewi Sartika Asrul; Lutfin, Nursakinah Annisa; Tuada, Rasydah Nur (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
The main focus of this research is to develop a digital learning media based on Mandar local culture to enhance the curiosity and scientific literacy of pre-service physics teachers. The development of the media employs the research and development (R&D) method using the 4D model (Define, Design, Develop, and Disseminate). The research subjects are pre-service physics teachers at a university in West Sulawesi. The developed digital media integrates elements of Mandar local culture, such as traditional maritime knowledge and shipbuilding technology, to stimulate students’ interest and understanding of scientific. Validation results indicate that the media is valid and practical for use in learning. A broad-scale trial showed a significant increase in both curiosity and scientific literacy. Therefore, this media is not only culturally relevant but also effective in supporting more engaging and contextual scientific learning for pre-service physics teachers.